A medicalização dos problemas de aprendizagem a partir da teoria sócio-histórica - Rentschler, Bianca (2022)
As a result of several social factors, health science, more specifically the study of neuroscience, has questioned pedagogical knowledge, considering it insufficient to explain learning problems. Taking away the protagonism of the educator and, many times, reducing the pedagogical knowledge to the detriment of the knowledge of medicine. The general objective of this research work is to analyze the process of medicalization of learning problems, from the Historical-Cultural theory and critical theories. In order to achieve this general objective, we set out as specific objectives (i) Recognize the importance of Historical-Cultural Psychology in the learning process, (ii) Problematize organicist base theories, based on Historical-Cultural Psychology, (iii) What are the differences between the biological view of hegemonic medicine and Vygotsky's Historical-Cultural theory. The corpus of this research is composed of literary reviews by: Moysés and Collares (1996, 1997, 2013), Moysés and Lima (1982), Guarido (2010), Caliman (2006, 2017), Vygotsky (1981, 1982, 1987, 1989, 2007, 2015, 2017), Machado (2007), Cosenza and Guerra (2011), Rotta T. and Bridi (2016), Lisbon (2014), Foucault (1995, 2008, 2002), Gaudenzi and Ortega (2012) and Illich (1975). Currently, referring students with learning difficulties to medical and psychological care is a common practice, largely carried out by professionals in the field of education, who are based on diagnostic assessments, understanding children's problems as individual, attributing the cause of failures in neurological activity. Pedagogical resources, mediation and all the methodological knowledge that teachers have are being disregarded in this scenario. The Historical-Cultural theory, as an alternative method, makes it possible to replace and overcome the pathologizing and biologizing ideas that determine what learning problems are based on genetic inheritance, reaching the main concept of the Historical-Cultural theory of the multiple relationships in which the individual it's inserted. The concepts of mediation, interaction, elementary and higher psychological functions presented by Vygotsky can bring many answers and many effective means of intervention.(AU)